2022
DOI: 10.1021/acs.bioconjchem.2c00232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Common Cell Culture Media Supplements on Citrate-Stabilized Gold Nanoparticle Protein Corona Formation, Aggregation State, and the Consequent Impact on Cellular Uptake

Abstract: Sodium citrate-stabilized gold nanoparticles (AuNPs) are destabilized when dispersed in cell culture media (CCMs). This may promote their aggregation and subsequent sedimentation, or under the proper conditions, their interaction with dispersed proteins can lead to the formation of a NP-stabilizing protein corona. CCMs are ionic solutions that contain growth substances which are typically supplemented, in addition to serum, with different substances such as dyes, antioxidants, and antibiotics. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Investigations of the internalization mechanism responsible for AuNP uptake suggested that this process was not significantly influenced by either clathrin receptors or lipid rafts. These findings indicate that under cell culture conditions, the primary factor influencing cellular uptake is NP aggregation [66].…”
Section: How Can We Exploit This Alliance?mentioning
confidence: 75%
See 1 more Smart Citation
“…Investigations of the internalization mechanism responsible for AuNP uptake suggested that this process was not significantly influenced by either clathrin receptors or lipid rafts. These findings indicate that under cell culture conditions, the primary factor influencing cellular uptake is NP aggregation [66].…”
Section: How Can We Exploit This Alliance?mentioning
confidence: 75%
“…CCMs are aqueous ionic solutions containing growth substances, often combined with various additives such as antioxidants, dyes, and antibiotics. Barbero et al conducted a study to examine the influence of additives, namely phenol red, penicillin-streptomycin, l-glutamine, and β-mercaptoethanol, on the development of the PC in cell culture media [66]. PCs with comparable characteristics were acquired, with the exception of the inclusion of antibiotics.…”
Section: How Can We Exploit This Alliance?mentioning
confidence: 99%
“…In-gel digestion protocol and liquid chromatography–mass spectrometry (LC-MS) analysis protocol were both performed as previously reported. 16 …”
Section: Methodsmentioning
confidence: 99%
“…In-gel digestion protocol and liquid chromatography-mass spectrometry (LC-MS) analysis protocol were both performed as previously reported. 16 Protein Identification and Quantitative Differential Analysis Protein identification and quantitative differential analysis protocols were adapted from previous reports. 17,18 Progenesis QI for proteomics software v3.0 (Nonlinear dynamics, UK) was used for MS data analysis using default settings.…”
Section: In-gel Digestion and Liquid Chromatography-mass Spectrometry...mentioning
confidence: 99%
“…Another key aspect is the type of biological fluid. Most studies investigate the BMC forming in serum or cell culture medium, [61,64,127,152,155,[204][205][206] but others use plasma (or directly in vivo) [64,65,70,207,208] or individual proteins. [193,205,209] Notably, different cell culture media (e.g., RPMI, DMEM) can lead to the formation of different GNP-BMCs.…”
Section: Analyzing the Proteomics Data For The Protein Corona Of Gnpsmentioning
confidence: 99%